Strategi Penggunaan Media Sosial Instagram sebagai Alat Komunikasi dalam Penguatan Branding One Media Digital tvOne - Putri Mahardhika Sakinah; Murtiadi Murtiadi; Roynaldi Arista (SABER : Jurnal Teknik Informatika, Sains dan Ilmu Komunikasi, 2025)
This study aims to enhance the utilization of One Media Digital tvOne by employing Instagram as a strategic communication tool. Instagram was chosen because of its strong visual and interactive characteristics as well as its large active user base in Indonesia, making it highly relevant in the context of strengthening the branding of digital television media. The focus of this research is to explore how tvOne leverages Instagram to reinforce its branding, increase audience participation, and build emotional closeness with its followers. The research adopts a descriptive qualitative approach with data collection techniques including in-depth interviews, participatory observation, and documentation. The informants consist of the tvOne social media team responsible for managing the official account, as well as active Instagram users who represent the primary audience. Two main theories support the analysis: Uses and Gratifications Theory, which emphasizes audience motives and satisfaction in media consumption, and Brand Awareness Theory, which relates to efforts in building awareness and audience loyalty toward a brand. The findings reveal that tvOne applies a consistent communication strategy through engaging visual content and the use of Instagram features such as reels, stories, and live streaming, combined with an interactive communication style. These strategies have proven effective in enhancing brand awareness, reinforcing a positive image, and cultivating audience loyalty. Personal approaches through direct interactions also foster a sense of emotional involvement among followers of the @tvonenews account. Thus, Instagram serves not only as an entertainment platform but also as a strategic communication device that continuously strengthens tvOne’s digital branding.